STUDI STABILITAS SEDIAAN SLEEPING MASK GEL MENGGUNAKAN EKSTRAK LIDAH BUAYA (Aloe vera L.) - Salsabila Azka Maharani; Florencia Yuwono; Stefani Yulia; Febriana Fitrianingsih; Anggoro Permadi Laksono; Shafira Putri; Anita Yuniarti; Shabrina Naurah Rayyani; Annisa Farida Muti; Andiri Niza Syarifah; Ade Abiyyatun Mahdiyyah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
The skin, as the largest organ of the body, serves a protective function and requires care to maintain its moisture and hydration. Sleeping mask gels are among the most effective nighttime skincare products, as they provide maximum hydration during sleep, have a texture that spreads easily, offer a cooling sensation, and can release active ingredients gradually. Aloe vera is widely recognized as an active cosmetic ingredient due to its content of flavonoids, saponins, and lignin, which help to moisturize the skin. This study aimed to evaluate the effect of varying concentrations of Aloe vera extract on the physical stability of sleeping mask gel formulations. Stability tests were conducted on days 0-28. Three gel formulas were prepared, each containing 0.75% carbopol 940. The results showed that F1 met stability criteria for organoleptic properties, spreadability, adhesiveness, and homogeneity, although changes in pH and viscosity occurred from day 7 to day 28. Statistical analysis indicated significant differences (p < 0.05) in viscosity among the formulas, while F1 showed no significant differences (p > 0.05) in spreadability and adhesiveness and maintained good consistency up to day 14. Based on these findings, F1 was considered more stable compared to F2 and F3.